Permasalahan Hukum Limbah Cair Industri di Indonesia - Haris Kusumawardana; Wahyu Hariadi; Agoes Djatmiko (Faculty of Law, Universitas Wijayakusuma, 2022)
Environmental problems will continue to appear seriously in various corners of the earth as long as the inhabitants of the earth do not immediately think about and seek environmental safety and balance. Likewise in Indonesia, it is as if environmental problems have been allowed to bubble up in line with the intensity of industrial growth, even though industrialization itself is becoming a priority in development. The complicated impression can be clearly seen if we try to pay attention to the responses and perceptions of the authorities regarding environmental problems, whether judges, prosecutors, police, lawyers, businessmen and the general public. The methodological approach used in this study is the normative juridical method, which is an approach that uses the concept of positive legality. Keywords: Law, Liquid Waste, Industry Abstrak. Permasalahan lingkungan hidup akan terus muncul secara serius diberbagai pelosok bumi sepanjang penduduk bumi tidak segera memikirkan dan mengusahakan keselamatan dan keseimbangan lingkungan. Demikian juga di Indonesia, permasalahan lingkungan hidup seolah-olah seperti dibiarkan menggelembung sejalan dengan intensitas pertumbuhan industri, walaupun industrialisasi itu sendiri sedang menjadi prioritas dalam pembangunan. Kesan pelik semakin jelas bisa dilihat apabila kita mencoba memperhatikan respon maupun persepsi para pihak yang berwenang mengenai permasalahan lingkungn hidup, baik hakim, jaksa, kepolisian, pengacara, pengusaha maupun masyarakat umum. Metodeologi pendekatan yang digunakan dalam penelitian ini adalah metode yuridis normatife, yaitu pendekatan yang menggunakan konsep legalitas positivtis. Kata Kunci: Hukum, Limbah Cair, Industri